2009
DOI: 10.1038/ejcn.2008.76
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of medium- and long-chain triacylglycerols decreases body fat and blood triglyceride in Chinese hypertriglyceridemic subjects

Abstract: Objectives: To investigate the effects of medium-and long-chain triacylglycerol (MLCT) on blood triglyceride (TG) in Chinese hypertriglyceridemic subjects. Methods: A double-blind controlled clinical trial was carried out, in which 112 subjects with hypertriglyceridemia were randomly divided into two dietary oil groups: (1) long-chain triacylglycerol (LCT) and (2) MLCT. All subjects were requested to ingest fixed energy and to continue their normal activity levels, and to consume LCT or MLCT oil at 25-30 g dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 31 publications
7
65
0
Order By: Relevance
“…Our results also show that MCT reduced the serum concentrations of triglyceride, total cholesterol, LDL-C and FFA. These results are in accordance with those of our previous clinical trial, 6,[9][10][11] although some studies have considered that the lipid metabolism of mice was no different from that of humans in certain respects. 25) The main explanations for the effect of MCT on reducing body fat accumulation are based on some results that MCT increased the energy expenditure in the body and accelerated fatty acid oxidation in the liver or WAT of rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also show that MCT reduced the serum concentrations of triglyceride, total cholesterol, LDL-C and FFA. These results are in accordance with those of our previous clinical trial, 6,[9][10][11] although some studies have considered that the lipid metabolism of mice was no different from that of humans in certain respects. 25) The main explanations for the effect of MCT on reducing body fat accumulation are based on some results that MCT increased the energy expenditure in the body and accelerated fatty acid oxidation in the liver or WAT of rats.…”
Section: Discussionsupporting
confidence: 93%
“…5) Many investigations during the past few years have reported that the intake of MCFA or MCT resulted in less body weight gain and body fat mass in animals and humans. [6][7][8][9] Our previous studies on humans have suggested that dietary oil containing MCFA could reduce in hypertriglyceridemic subjects the body weight, body mass index (BMI), body fat mass, waist circumference (WC), hip circumference (HC) and waist-hip ratio when compared to oil containing LCFA, and that these effects were much better in subjects who were male, overweight and less than 60 years old. 6,10,11) MCT has been considered to have potential for preventing and treating obesity, although the mechanism was not fully understood.…”
mentioning
confidence: 99%
“…14,[17][18][19][20] Moreover, apolipoprotein profiles in the blood were also improved greatly in Chinese hypertriglycerideamic subjects. 22) In the present study, we found that MLCT lowered body weight and body fat weight only in the hypertriglycerideamic subjects of age less than 60 years, not in those more than 60 years. Although older subjects enrolled and some of the subjects dropped out, the body compositions of the younger subjects in the MLCT group were significantly different from the initial values, but this was not significant in the older subjects at the end of the study.…”
Section: Discussionsupporting
confidence: 44%
“…8,21) We have reported that MLCT reduced blood TG in Chinese hypertriglycerideamic subjects. 22) These different results might be attributed to the different subjects chosen. The ages of the subjects might be an important factor.…”
mentioning
confidence: 99%
“…Among these, butyric acid is the best known for its biological functions. Butyric acid is a substrate for growth and regeneration of cells in the large intestine; it has anti-cancer properties in colon cancer, probably enhancing apoptosis of tumoral cells, and more importantly for the purpose of this review, it increases thermogenesis, energy expenditure and contributes to the reduction of body weight and other factors present in the metabolic syndrome (Goncalves and Martel, 2013;Liu et al, 2011;Xue et al, 2009). …”
Section: Short-and Medium-chain Fatty Acidsmentioning
confidence: 99%